Self-care behaviour and associated factors among chronic heart failure clients on follow up at selected hospitals of Wollega zones, Ethiopia. (2021) - Fetensa, Getahun; Fekadu, Ginenus; Turi, Ebisa; Tolossa, Tadesse; Wakuma, Bizuneh; Etefa, Werku; Habte, Ashenafi; Yadecha, Birhanu; Bekele, Firomsa
Abstract: Background: Effective prevention and treatment of heart failure needs good knowledge of cardiovascular diseases (CVD) conditions and their risk factors. However, in developing countries such as Ethiopia, the levels of knowledge and awareness for CVD and risk factors were generally near to the ground. Objective: To assess self-care behaviour and its associated factors among heart failure (HF) patients on follow up at Wollega zones public hospitals, Ethiopia. Methods: Hospital based cross-sectional study was employed. The data was entered into Epi-data version 3.1 and analyzed using SPSS windows version 24.0. Variable with p-value<0.05 at multi variable analysis was taken as significant variable for self-care behavior. Results: Among 424 study participants, (57.1%) were females and the mean age (±SD) of the respondent was 46.25 ± 17.047 years. About half, 51.2 % (95% CI; 46.1–56.3) of heart failure patients reported good adherence to their self-care recommendations. Urban residence (AOR = 3.49, 95% CI: 2.044–5.7) and duration of heart failure greater than one year (AOR = 1.758, 95% CI; 1.057–2.924) were positively associated with good to self-care recommendation. Whereas, presence of co-morbidity (AOR = 0.099, 95% CI; 0.053–0.184), female sex (AOR = 0.186, 95%CI; 0.096–0.362) and side effect of the drugs (AOR = 0.118, 95% CI: 0.025–0.557) were negatively associated with good to self-care behavior up on multivariable logistic regression. Conclusion: Substantial proportion of heart failure patients had poor self-care behavior adherence. Provision of health education and counseling to clients with heart failure will play a paramount role.